Apophatic Theology of God’s Incomprehensible Trinitarianism as Seen by Vladimir N. Lossky - Michał Płóciennik (Collectanea Theologica)
The purpose of this text is to present the apophatic struggle with the incomprehensible mystery of God’s trinitarianism by one of the most eminent Orthodox theologians of the 20th century, and a radical defender of the apophatic nature of Christian theology, Vladimir N. Lossky. It consists of six sections. The subject of the first will be the original facticity, the givenness of the Trinity. The second will examine the question of the monarchy of the Father as the Source of the Trinity. This will be followed by a look at the issue of the relationship between the Divine Persons and Trinitarian distinctions. The fourth section will look at the aporia Filioque and its significance in understanding the being of God and the influence it has played in the division of Christianity. The fifth section will attempt a critical dialogue with the presented aspects of Lossky’s thought in the key of the hermeneutics of theological differences between the East and the West – this key will constitute the content of the sixth chapter-supplement. In conclusion, it will be articulated the contemplative and deifying character of apophatic theology, which aims at the unknowable and supra-conceptual, incomprehensible Trinity.